Особенности десорбции газа из поровой структуры ископаемых углей - Кириллов, А.К. (Физико-технические проблемы горного производства, 2005)
Пропонується враховувати нелінійність рівняння дифузії для процесу десорбції. Показано можливість такого підходу при аналізі кривих десорбції метану. It is offered to take into account nonlinearity of the equation of diffusion for process desorption. The opportunity of such the point of view is shown at the analysis of the methane desorption curves.